2015
DOI: 10.1093/femsec/fiv133
|View full text |Cite
|
Sign up to set email alerts
|

Scale-dependent effects of climate and geographic distance on bacterial diversity patterns across northern China's grasslands

Abstract: Patterns of variation in plant and animal diversity along precipitation gradients have been extensively studied, but much less is known about how and to what extent precipitation affects the biogeographic distribution of microbial diversity in arid areas across large spatial scales. Here we collected soils from 54 sites along a 3700 km transect covering a wide range of grassland ecosystems with distinct aridity gradients. We quantified the bacterial community diversity and the effects of climate, edaphic param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
78
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(96 citation statements)
references
References 70 publications
(41 reference statements)
17
78
1
Order By: Relevance
“…Firstly, most of bacterial species were homogeneously shared by the desert, typical, and meadow steppes and the unique species in specific steppe were very few. Although it has been reported that soil characteristics were important factors in shaping soil bacterial communities (Griffiths et al, 2011;Lauber et al, 2009), climate conditions and plantation could also cause some shifts of bacterial communities (Leff et al, 2018;Wang et al, 2015), interestingly, these factors did not show clear influence on the bacterial compositions in the steppes in the current work. The question is which factor would be more important in relation to the distributions of bacterial compositions between the steppes.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Firstly, most of bacterial species were homogeneously shared by the desert, typical, and meadow steppes and the unique species in specific steppe were very few. Although it has been reported that soil characteristics were important factors in shaping soil bacterial communities (Griffiths et al, 2011;Lauber et al, 2009), climate conditions and plantation could also cause some shifts of bacterial communities (Leff et al, 2018;Wang et al, 2015), interestingly, these factors did not show clear influence on the bacterial compositions in the steppes in the current work. The question is which factor would be more important in relation to the distributions of bacterial compositions between the steppes.…”
Section: Discussioncontrasting
confidence: 65%
“…The geographic locations of the steppes follow the order of meadow, typical, and desert steppes from the east to the west of Inner Mongolia. This would imply a possible interpretation, the desert and typical steppes, and typical and meadow steppes were adjacent; they possessed high bi‐shared microbial communities (Wang et al, ). Furthermore, few bi‐shared microbial communities that detected between these two ecosystems might also be linked to the transitions of a few grass species and climate conditions between them (Yan et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Whether the processes and factors that control the spatial patterns of macro-organisms, such as contemporary environmental conditions and historical contingencies, also apply to micro-organisms remains unclear (Ge et al, 2008;Martiny et al, 2006;Ramette & Tiedje, 2007). Recent studies have documented a wide range of biotic and abiotic factors that influence microbial diversity and community structure such as soil pH (Chu et al, 2010;Fierer & Jackson, 2006;Lauber, Hamady, Knight, & Fierer, 2009), vegetation (Peay, Baraloto, & Fine, 2013), temperature , and aridity (Wang et al, 2015). However, as noted by Ge et al (2008) and de Vries et al (2012), most studies have documented the variation and potential patterns of microbial diversity under certain ecological variation or gradient.…”
Section: Introductionmentioning
confidence: 99%
“…According to Vellend's conceptual synthesis of community ecology (Vellend, ), dispersal refers to the movement of organisms across space; selection represents the changes in community structure caused by deterministic fitness differences between taxa; drift reflects stochastic changes in the relative abundances of different taxa; diversification produces new genetic variation. There is increasing awareness that all of these processes operate in combination to assemble the community; however, their relative importance varies across different spatial scales (Martiny, Eisen, Penn, Allisona, & Horner‐Devine, ; Wang et al., ) and habitat types (Wang et al., , ). Recently, evidence has shown that the relative importance of the individual drivers of microbial community assembly also varies between different taxa (Brown & Jumpponen, ).…”
Section: Introductionmentioning
confidence: 99%